2015
DOI: 10.7314/apjcp.2015.16.4.1535
|View full text |Cite
|
Sign up to set email alerts
|

Is it Necessary to Submit Grossly Normal Looking Gall Bladder Specimens for Histopathological Examination?

Abstract: Background: The objectives of the study were to: 1) determine the frequency of incidental malignancy in unsuspected/grossly normal looking gall bladders; 2) determine the frequency of malignancy in suspected/grossly abnormal looking gall bladders. Materials and Methods: This prospective, cross sectional study was carried out at a tertiary care hospital in Pakistan, during a four year period (Jan 2009-dec2012). All the cholecystectomy cases performed for gallstone diseases were examined initially by a surgeon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…Bazoua et al, Emmett et al, and Darmas et al have reported incidental GBC rates of 0.17% (5/2890), 0.25% (12/4776), and 0.27% (4/1452), respectively (7-9). Tayeb et al have noted incidental GBC in only 3 out of 426 (0.70%) cases (10). All cases of incidental GBC in these studies had a macroscopically abnormal gallbladder; hence, these studies suggest that it is safe to adopt a selective approach to Some studies showed that it may be justified to exclude gallbladder specimens from the HPE by using macroscopic examination.…”
Section: Discussionmentioning
confidence: 89%
“…Bazoua et al, Emmett et al, and Darmas et al have reported incidental GBC rates of 0.17% (5/2890), 0.25% (12/4776), and 0.27% (4/1452), respectively (7-9). Tayeb et al have noted incidental GBC in only 3 out of 426 (0.70%) cases (10). All cases of incidental GBC in these studies had a macroscopically abnormal gallbladder; hence, these studies suggest that it is safe to adopt a selective approach to Some studies showed that it may be justified to exclude gallbladder specimens from the HPE by using macroscopic examination.…”
Section: Discussionmentioning
confidence: 89%
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…The authors regarded this policy as effective and safe and there is no possibility to miss any case of invasive adenocarcinoma if only macroscopically abnormal specimens were sent for histopathological examination. [10][11][12][13][14]17,18] In this regard, the safe management of the patient, cost-effectiveness, and the histopathologist's workload should be appreciated. In our study, out of 1176 specimens, only five (0.4%) cases of primary invasive gall bladder adenocarcinoma were found.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Hence, it has been recommended to submit all gallbladders to routine histopathological examination. [9] However, the role of routine histopathological examination of all cholecystectomy specimens has been revised by many authors [10][11][12][13][14]17,18] This study was conducted to assess the necessity for routine histopathological examination of all Cholecystectomy specimens and to call attention to selective criteria for sending gallbladders to the histopathological examination following cholecystectomy without affecting the patients' safety. Such a selection aims to reduce the number of gallbladders sent for histopathological examination in order to save time, coast and burden on the histopathologists.…”
Section: ‫احيا‬ ‫جر‬ ‫الة‬ ‫المز‬ ‫ارة‬ ‫المر‬ ‫عينات‬ ‫لجميع‬ ‫الروتmentioning
confidence: 99%